2020
DOI: 10.1086/706253
|View full text |Cite
|
Sign up to set email alerts
|

Deer Indirectly Alter the Reproductive Strategy and Operational Sex Ratio of an Unpalatable Forest Perennial

Abstract: Environmental conditions impose restrictions and costs on reproduction. Multiple reproductive options exist when increased reproductive costs drive plant populations toward alternative reproductive strategies. Using 4 years of demographic data across a deer impact gradient, where deer alter the abiotic environment, we parameterize a size-dependent integral projection model for a sexually labile and unpalatable forest perennial to investigate the demographic processes driving differentiation in the operational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Our results are also consistent with the notion that flowering through the female function (in P. alpina , this means adopting a hermaphroditic rather than a male phase in a given season) places a heavier burden on a plant’s resources than flowering just through its male function (Schlessman 1991; Zhang et al 2014; Bialic-Murphy et al 2020): smaller plants were more likely to produce a single male flower, whereas larger plants produced more flowers and flowers with both male and female functions. Indeed, we found that larger individuals of P. alpina made a greater absolute and relative allocation to their female function than smaller plants, with a significantly steeper positive slope of absolute allocation to the female than male function.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results are also consistent with the notion that flowering through the female function (in P. alpina , this means adopting a hermaphroditic rather than a male phase in a given season) places a heavier burden on a plant’s resources than flowering just through its male function (Schlessman 1991; Zhang et al 2014; Bialic-Murphy et al 2020): smaller plants were more likely to produce a single male flower, whereas larger plants produced more flowers and flowers with both male and female functions. Indeed, we found that larger individuals of P. alpina made a greater absolute and relative allocation to their female function than smaller plants, with a significantly steeper positive slope of absolute allocation to the female than male function.…”
Section: Discussionsupporting
confidence: 89%
“…alpina, this means adopting a hermaphroditic rather than a male phase in a given season) places a heavier burden on a plant's resources than flowering just through its male function (Schlessman 1991;Zhang et al 2014;Bialic-Murphy et al 2020): smaller plants were more likely to produce a single male flower, whereas larger plants produced more flowers and flowers with both male and female functions. Indeed, we found that larger individuals of P.…”
Section: The Mating System and Inbreeding Depression In P Alpinamentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that while some variation will always arise, much larger differences have likely arisen in recent centuries as densities of larger fauna, such as elephants, have fluctuated far outside prehistoric norms as populations have been eliminated from some forests and restricted to others (Sheil 2020). The consequences of variable conditions on dioecious populations remain an important subject of research (Bialic-Murphy et al 2020, Tonnabel et al 2017.…”
Section: Size and Damagementioning
confidence: 99%
“…To capture the effect of the Alliaria treatment on plant growth, we randomly selected N = 501 individuals across the three species and measured aboveground size in June-July in 2018 and 2019. Plant biomass was estimated using speciesspecific allometric equations previously developed (Brouwer et al 2015;Bialic-Murphy et al 2019;Bialic-Murphy et al 2020).…”
Section: Whole-plant Performancementioning
confidence: 99%